PENGGUNAAN PRINSIP REBUS SIC STANTIBUS DALAM PEMBATALAN PERJANJIAN LAUT TIMOR (CERTAIN MARITIME ARRANGEMENTS IN THE TIMOR SEA / CMATS) ANTARA TIMOR LESTE DENGAN AUSTRALIA: THE APPLICATION OF THE REBUS SIC STANTIBUS PRINCIPLE IN THE CANCELLATION OF THE TIMOR SEA TREATY (CERTAIN MARITIME ARRANGEMENTS IN THE TIMOR SEA / CMATS) BETWEEN TIMOR LESTE AND AUSTRALIA - Wardhana, Muhammad Raihan; Nrangwesti, Ayu (Fakultas Hukum Universitas Trisakti, 2025)
International agreements generally have two types of international agreements, namely multilateral and bilateral, which are seen from the number of parties. In the case of the CMATS agreement, it is included in the type of bilateral international agreement because the countries involved are two countries. In international agreements, there are principles that must be present in every agreement, namely the principles of Good Faith, Pacta Sunt Servanda, Jus Cogens, Rebus Sic Stantibus. The CMATS agreement has been canceled by Timor Leste. This raises the problem, namely whether the cancellation is in accordance with the principles of international treaty law and whether the Rebus Sic Stantibus principle can be used in its cancellation. The purpose of the study is to explain the cancellation of CMATS with several principles of international agreements and explain the use of Rebus Sic Stantibus in its cancellation. The research method used is normative juridical, with an analytical descriptive approach, and qualitative data processing. The results of the study show that in addition to several principles used in making an international agreement, these principles can also be used as reasons for canceling an international agreement. Australia is considered to have violated the three principles. This is because Australia committed espionage which caused losses to Timor Leste. The losses that make Timor Leste able to cancel the CMATS Agreement. The Rebus Sic Stantibus principle can be used by Timor Leste as a reason to cancel the CMATS Agreement. The cancellation of the CMATS agreement by Timor Leste is in accordance with the principles of International Treaty law, namely the principle of Good Faith and Pacta Sunt Servanda. The conclusion of the study concludes that, first, the cancellation of the CMATS agreement is in accordance with the principles of International Treaty Law. Second, Rebus Sic Stantibus can be used as a basis for Timor Leste to cancel the CMATS Agreement.